GIS and infographic applications in the North House of Arucci archaeological site (Aroche, Huelva) - Álvaro Corrales Álvarez; Javier Bermejo Meléndez; Juan M. Campos Carrasco (Virtual Archaeology Review, 2018)
The present paper is focused on the application of a methodological model specifically designed to develop the tasks related to analysis and dissemination of the Roman Hispania site of Arucci (Aroche, Huelva). The main aim of our approach is to reconcile the diffusion of the results obtained after the excavation, documentation, and the study of the archaeological record with the methodological analysis of a Geographic Information System (GIS). We consider that a GIS is the most appropriate tool in archaeology for this purpose since it allows users to manage a large amount of data in diverse formats and insert it in a closed topographic reference frame. For that purpose, we restrict the field of action to the North House (a house built in the time of Emperor Augustus that lasted until the 3rd century AD). The real power of this research relies on the integration of the digital building archaeological record in a GIS, while the architecture of the Roman house is reconstructed virtually from archaeological remains, in this way the domestic space is visually comprehensible. According to the results obtained in this pilot experience, we can affirm that the union of GIS and infographics allows archaeological reality to surpass the strictly academic scope and promote it to society making possible the Arucci site approachable to professionals of archaeology as well as to the uninitiated. The feasibility of the proposal that was carried out within the North House encourages us to consider the export of this study model to the rest of buildings that make up the site such as the foro, macellum, balneum as, well as other domus.